Islamic Microfinance in Indonesia - Hans Dieter Seibel; Wahyu Dwi Agung (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2006)
Indonesia, the largest Muslim country, has a highly differentiated micro- and rural finance sector which has evolved over more than a century. Islamic finance has emerged in 1991, comprising Islamic commercial banks and banking units, rural banks, and financial cooperatives. In this study we deal with the emerging Islamic microfinance sector in Indonesia, particularly rural banks and financial cooperatives: how they have evolved, how they compare with conventional institutions, and what their prospects for growth are.
Keywords: 330